Responses of Polyamine-Metabolic Genes to Polyamines and Plant Stress Hormones in Arabidopsis Seedlings - Yusaku Yariuchi; Takashi Okamoto; Yoshiteru Noutoshi; Taku Takahashi (Cells, 2021)
In plants, many of the enzymes in polyamine metabolism are encoded by multiple genes, whose expressions are differentially regulated under different physiological conditions. For comprehensive understanding of their regulation during the seedling growth stage, we examined the expression of polyamine metabolic genes in response to polyamines and stress-related plant hormones in Arabidopsis thaliana. While confirming previous findings such as induction of many of the genes by abscisic acid, induction of arginase genes and a copper amine oxidase gene, CuAOα3, by methyl jasmonate, that of an arginine decarboxylase gene, ADC2, and a spermine synthase gene, SPMS, by salicylic acid, and negative feedback regulation of thermospermine biosynthetic genes by thermospermine, our results showed that expressions of most of the genes are not responsive to exogenous polyamines. We thus examined expression of OsPAO6, which encodes an apoplastic polyamine oxidase and is strongly induced by polyamines in rice, by using the promoter-GUS fusion in transgenic Arabidopsis seedlings. The GUS activity was increased by treatment with methyl jasmonate but neither by polyamines nor by other plant hormones, suggesting a difference in the response to polyamines between Arabidopsis and rice. Our results provide a framework to study regulatory modules directing expression of each polyamine metabolic gene.